2001
DOI: 10.1074/jbc.m102187200
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Valine for Leucine 305 in Factor VIIa Increases the Intrinsic Enzymatic Activity

Abstract: Factor VII requires the cleavage of an internal peptide bond and the association with tissue factor (TF) to attain its fully active factor VIIa (FVIIa) conformation. The former event alone leaves FVIIa in a zymogen-like state of relatively low specific activity. We have designed a number of FVIIa mutants with the aim of mimicking the effect of TF, that is, creating molecules with increased intrinsic (TF-independent) enzymatic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 25 publications
5
55
0
1
Order By: Relevance
“…Under these conditions, the apparent velocity of FX hydrolysis by FVIIaWT was significantly higher than that of FVIIa303T. This finding suggests that the conformational equilibrium FVIIa « FVIIa*, where FVIIa is the zymogen-like form and FVIIa* is the functionally active form of the FVIIa molecule (Dennis et al, 2000Persson et al, 2001a;Roberge et al, 2001;Sichler et al, 2002), is severely shifted to the right. The perturbation of this conformational equilibrium is even more evident in the presence of TF, whose binding is unable to shift the conformational transition toward a fully active FVIIa form.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Under these conditions, the apparent velocity of FX hydrolysis by FVIIaWT was significantly higher than that of FVIIa303T. This finding suggests that the conformational equilibrium FVIIa « FVIIa*, where FVIIa is the zymogen-like form and FVIIa* is the functionally active form of the FVIIa molecule (Dennis et al, 2000Persson et al, 2001a;Roberge et al, 2001;Sichler et al, 2002), is severely shifted to the right. The perturbation of this conformational equilibrium is even more evident in the presence of TF, whose binding is unable to shift the conformational transition toward a fully active FVIIa form.…”
Section: Discussionmentioning
confidence: 53%
“…Globally, these exosites are referred to as the 'activation domain' and encompass residues 284-294, 295-304, 332-345 and 363-374 (Eigenbrot et al, 2001). Studies of the mutations of FVII showed that the substitutions M298Q (Petrovan & Ruf, 2001), R304Q (O'Brien et al, 1991), R304W (Matsushita et al, 1994), L305V (Persson et al, 2001a), and M306D (Persson et al, 2001b) in the serine protease domain had adverse effects on the enzyme's activity and TF interaction. Indeed, the R304Q and R304W mutations were associated with reduced affinity for human TF and reduced FVIIa activity, while the L305V, M306D and M298Q mutations increase FVIIa activity even in the absence of TF, without altering the TF affinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following substitution of amino acids in vicinity to this region, namely Leu305Val and Phe374Pro, slightly increased amidolytic and proteolytic activity by 4-fold and 1.5-fold, respectively, mediating a local reorganization of the helix [10]. More potent variants were generated by introducing amino acids which can be found in thrombin possessing a considerable constitutive activity.…”
Section: Engineering Fviia Variants With Increased Intrinsic Activitymentioning
confidence: 99%
“…The complex formation is an essential process in which TF allosterically leads to a fully active FVIIa [9]. The cleavage alone leaves FVIIa in a zymogen-like conformation of quite low specific activity [3,10]. Several residues in the first EGF-like domain of FVII and in the protease domain, especially methionine at position 306, seem to be pivotal for the cofactor-mediated allosteric stimulation [11].…”
Section: Fvii/fviiamentioning
confidence: 99%